2007
DOI: 10.2166/wst.2007.729
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic anaerobic digestion in compact systems: investigations by modern microbiological techniques and mathematical simulation

Abstract: Thermophilic anaerobic digestion in compact systems can be an economical and ecological reasonable decentralised process technique, especially for rural areas. Thermophilic process conditions are important for a sufficient removal of pathogens. The high energy demand, however, can make such systems unfavourable in terms of energy costs. This is the case when low concentrated wastewater is treated or the system is operated at low ambient temperatures. In this paper we present experimental results of a compact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…These results might indicate that the temperature prediction should be improved. In this respect, previous reports [5,7] have shown that methane yield can decrease between 11.2 and 6.0%°C -1 when a temperature reduction takes place. This suggests that a minimization in the prediction error of the temperature variation could reduce the prediction error of the methane yield prediction.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…These results might indicate that the temperature prediction should be improved. In this respect, previous reports [5,7] have shown that methane yield can decrease between 11.2 and 6.0%°C -1 when a temperature reduction takes place. This suggests that a minimization in the prediction error of the temperature variation could reduce the prediction error of the methane yield prediction.…”
Section: Resultsmentioning
confidence: 76%
“…That situation allows to infer that thermophilic anaerobic digestion (TAD) could be easily affected by environmental conditions. In this respect, two independent research groups [5,7] reported that, under TAD, methane yield decreases between 6 and 11.16%°C -1 when a temperature reduction takes place. This could be attributed to the strong dependence on temperature of the kinetic parameters of the reactions involved in anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mikrobiologische Studien über die Population der Bakterien zeigen, dass die Vielfalt und Zusammensetzung der Population sehr komplex und variabel sind [31,32]. In der Praxis erhöht sich die Konzentration der Bakterien im Reaktor, wenn Gülle statt Abwasser als Substrat verwendet wird [28].…”
Section: Anpassung Der Aktiven Biomasseunclassified
“…This finding corresponds very well with results revealed by Kim et al (2003), who observed the highest methane production rate in co-digestion of sewage sludge with food waste in the range of 30-40% VS under mesophilic conditions. Reports on full-scale sludge co-digestion practices are scarce in the peer-reviewed literature and mainly focusing on technical requirements and economic efficiency (Björnsson et al, 2000;Dereli et al, 2010;Krupp et al, 2005;Lübken et al, 2007;Park et al, 2011). Mata-Alvarez et al (2014) assume that this is likely due to the low interest of the industrial sector to publish their results in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%